FAHR’S SYNDROME DUE TO IDIOPATHIC HYPOPARATHYROIDISM WITH VITAMIN D DEFICIENCY, HYPOMAGNESEMIA, AND PRIMARY HYPOTHYROIDISM - Budoyo, Didik Supriyadi Kusumo; Ikhsan, M. Robhikul (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Fahr’s syndrome due to hypoparathyroidism is a rare condition with a prevalence of 23-37 cases per 100,000 people per year. A 63-year-old Indonesian female had frequent seizures, hallucinations, depression, and dementia. Peripheral blood, liver and kidney function, and blood glucose were normal. Hypocalcemia and hypothyroidism were observed. Head CT scan revealed intracerebral calcifications. The serum magnesium level was decreased while serum calcium levels were always low despite repeated corrections. She was later diagnosed with vitamin D deficiency and hypoparathyroidism. We gave CaCO3, calcitriol, vitamin D3, levothyroxine, haloperidol, and phenytoin. She was then deemed stable for outpatient care. Almost 73.8% of hypoparathyroid patients have basal ganglia calcifications, while two cohort studies in America and India reported 52-74%. Therapy aims to achieve serum calcium at the low-normal range to reduce symptoms and prevent the worsening of brain calcification. PTH replacement therapy is indicated for our patient but we provided conventional therapy with monitoring of hypercalciuria every 6 months. It is important to find the etiology of Fahr’s syndrome and prevent complications due to therapy.